Reading Clinic Program at SD Negeri 2 Mantren: A Quantitative Descriptive Study - Rois Ageng Ayu Saputri; Syamsul Sodiq (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the implementation of the reading clinic program at SD Negeri 2 Mantren, to determine students' learning motivation after participating in the program, and to determine student learning outcomes after the activity. The study was conducted at SD Negeri 2 Mantren in 2025 using a descriptive quantitative approach. The population in this study was 58 students, namely all students participating in the reading clinic program, while the sample size was 17 students. Data were collected through observations of teacher activities, a learning motivation questionnaire, and a final test. Data analysis was conducted using descriptive statistics using percentages to describe program implementation, levels of learning motivation, and student learning outcomes. The results showed that the program was very successful, as evidenced by a score of 98% for teacher observations, indicating that all stages of the EGRA assessment, the use of multisensory media, and repeated reading techniques were implemented appropriately and systematically. The results of the learning motivation questionnaire showed a percentage of 94.51%, indicating that students felt happy, confident, received emotional support from their teachers, and demonstrated high enthusiasm in participating in the program. Furthermore, the final test result of 88.23% indicated an improvement in basic reading skills. Overall, the reading clinic program has been proven to improve students' learning motivation and reading skills through targeted and systematic mentoring.